From vision to action and evaluation: Role of governance and stakeholder engagement in nurturing green sSchools in India - Arora, Meenal (American Journal of STEM Education, 2026)
The concept of a ‘green school’ integrates education for sustainable development into all aspects of school life, involving the entire school community. The researcher analyzed 19 global resources on green schools using framework analysis to identify the best strategies for governance and stakeholder engagement in energy, food, water, waste, and biodiversity. A thematic framework was developed, and tools were created for data collection from state-run residential schools in the Delhi NCR, India. The results present governance strategies, including vision, mission, objectives, and values, that guide green practices. It also includes action plans that delineate roles, set goals, audit performance, engage the community, and report achievements. Monitoring and evaluation strategies use quantitative and qualitative data to assess progress, fostering comprehensive change.